2019
DOI: 10.1097/md.0000000000017444
|View full text |Cite
|
Sign up to set email alerts
|

Infectious keratitis secondary to canaliculitis with concretions

Abstract: Rationale:Canaliculitis is a frequently overlooked and misdiagnosed disease. Concurrent corneal ulceration with canaliculitis is uncommon. We report such a case.Patient concerns:An 87-year-old woman complained of swelling and pain of the right eye after acute angle closure glaucoma attack. Slit-lamp examination was compatible with the features of infectious keratitis, and the cultures from corneal scrapings grew Streptococcus anginosus later. Hourly topical vancomycin (25 mg/ml) was instilled, then the corneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…[ 16 ] Canaliculitis-induced corneal inflammation, lysis, and perforation, though reported previously, are also relatively rare. [ 18 ] Lacrimal system infections may resemble autoimmune disease-induced PUK as recently reported by Ishimoto et al . [ 19 ] The corneal lysis was thought to be due to an inflammatory reaction against toxin released by the pathogen.…”
Section: Discussionmentioning
confidence: 81%
“…[ 16 ] Canaliculitis-induced corneal inflammation, lysis, and perforation, though reported previously, are also relatively rare. [ 18 ] Lacrimal system infections may resemble autoimmune disease-induced PUK as recently reported by Ishimoto et al . [ 19 ] The corneal lysis was thought to be due to an inflammatory reaction against toxin released by the pathogen.…”
Section: Discussionmentioning
confidence: 81%
“…In this report, all six patients with corneal perforation and lacrimal canaliculitis were female, and most of them were aged 70 years or above. Previous studies have reported two male cases and six female cases of corneal perforation associated with canalliculitis 13 , 14 , 16 , 17 It is possible that corneal perforation caused by lacrimal canaliculitis is much more common in females. A possible explanation is the preponderance of lacrimal duct diseases, including canaliculitis, in older females.…”
Section: Discussionmentioning
confidence: 97%
“… 21 , 22 In two cases of corneal ulcer associated with lacrimal canaliculitis, the same organism was isolated from the cultures of corneal scraping and canalicular discharge. 17 , 23 In another study of 35 patients with keratitis and nasolacrimal duct obstruction, the same organism was cultured from corneal scraping and mucopurulent material in the lacrimal sac. 24 In our case series, cultures of corneal scrapings at the perforation sites yielded no microorganisms, although most cultures of canalicular discharge were positive for bacteria or fungi.…”
Section: Discussionmentioning
confidence: 99%
“…These reports include orbital cellulitis with subperiosteal abscess, 9,10 endogenous endophthalmitis, 11,12 severe Lemierre syndrome with venous hypertension, and vasculitis that eventually causes blindness, 13 as well as infectious keratitis secondary to canaliculitis. 14 Cavernous sinus thrombosis is common during the infection. 10,15 The patient first presented to our clinic with the most obvious manifestation of left eye proptosis and ptosis.…”
Section: Discussionmentioning
confidence: 99%